(3TQM efXheI ZQGei UMjMs - (3jMji Hf YHO GdQMef GdbQGai GdCUagGfjs; (3GHf aQM , CMeO Hf aQM Hf CMeO Hf eMeO Hf aQM GddNej GdGTHjdj, TgGH GdOjf CHh GdYHGS,J (B966 (3g` s ((3ESeGYjd Hf QLH Hf jhSa GdfGHdSi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf bGd abjQ QHg GdcGai jMji GdbQGai Hf YHO GdQMef GdCUagGfi GdMeO ddg GdPi bHd HUMjM GdfjI ef gGLQ Edjg hcai HMSfgG ef Jhcd Ydjg hHYO agPG TQM dWja GdMLe YdbJg Ydi efXheI GdMGaX GHf aQL GdETHjdi s
(3BNQgG (B:s
(3bGd Pdc jMji (B( (3Hf (B) (3YHO GdQMef GdCUagGfi CLGQg Gddg JYGdi hcaGg eG Cgeg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B45s
Keywords: (3GdMOjK h GdeUWdMs